2010
DOI: 10.1039/c0cp00918k
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a large negative temperature dependence for rate coefficients of reactions of OH with oxygenated volatile organic compounds studied at 86–112 K

Abstract: The rate coefficients (k) for reactions of OH with acetone, methyl ethyl ketone (MEK) and dimethyl ether (DME) have been measured in the temperature range 86-112 K using a pulsed Laval nozzle apparatus. Large increases in k at lower temperatures were observed, with k(86K)/k(295K) = 334 for acetone, and k(93K)/k(295K) = 72 and 3, for MEK and DME respectively. A mechanism involving the formation of a hydrogen bonded complex prior to an overall barrier on the potential energy surface is proposed to explain this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 16 publications
10
69
2
2
Order By: Relevance
“…These results further highlight the role that a pre-reaction hydrogen bonded OH complex plays in low temperature kinetics, in this case the adduct is sufficiently long lived to facilitate tunnelling, the majority proceeding via the higher activation barrier to form CH 3 O. In previous studies, for example of the reaction between OH with acetone, we had also observed a dramatic increase in the rate coefficient at very low temperatures [28], although a significant pressure dependence of the rate coefficient suggested collisional stabilisation of the complex without tunnelling to products [26].…”
Section: Discussionmentioning
confidence: 68%
“…These results further highlight the role that a pre-reaction hydrogen bonded OH complex plays in low temperature kinetics, in this case the adduct is sufficiently long lived to facilitate tunnelling, the majority proceeding via the higher activation barrier to form CH 3 O. In previous studies, for example of the reaction between OH with acetone, we had also observed a dramatic increase in the rate coefficient at very low temperatures [28], although a significant pressure dependence of the rate coefficient suggested collisional stabilisation of the complex without tunnelling to products [26].…”
Section: Discussionmentioning
confidence: 68%
“…14,17,22 Furthermore, the formation of the longer-lived complex at low temperature enhances the probability of hydrogen atom transfer via quantum mechanical tunneling to form products. It is postulated that this mechanism may be general for reactions of OH with oxygenated volatile compounds, and that these reactions should be considered in networks describing the chemistry of the interstellar medium.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent low temperature studies of neutral-neutral reactions have shown that the temperature dependence of their rate coefficients is often complex and poorly understood, and so kinetic data close to ambient temperatures cannot simply be extrapolated. [14][15][16][17] From previous studies it is acknowledged that at temperatures above 200 K, the reactions of OH with alcohols appear to proceed via a direct, bimolecular hydrogen abstraction mechanism (R1). 2,6,17,18 + R1…”
Section: Introductionmentioning
confidence: 99%
“…The experimental setup of the pulsed Laval nozzle apparatus utilised in this study has been discussed in detail previously so only a brief description is given here [12][13][21][22] . Methanol was degassed and its vapour pressure was admitted to an evacuated cylinder where it was diluted with N 2 (Ar) and allowed to mix overnight before use.…”
Section: Plp-lif-laval Nozzlementioning
confidence: 99%